2006
DOI: 10.1590/s0021-75572006000200011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de rinite alérgica em adolescentes do Distrito Federal: comparação entre as fases I e III do ISAAC

Abstract: Objectives: To determine the prevalence of allergic rhinitis in a random group of schoolchildren aged 13 to 14 years in Brasilia, Brazil, to evaluate tendencies over 6 years and to compare prevalence rates among different socioeconomic groups. Methods:Two cross-sectional studies were undertaken 6 years apart, using the ISAAC (phases I and III) written questionnaire. Thirty-nine schools were chosen at random from eight administrative regions in Brasilia, and were classified into three groups according to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
1
0
4
Order By: Relevance
“…In the epidemiology of allergic illnesses, the presence of a socioeconomic gradient has been observed, with a higher prevalence of allergic rhinitis and eczema among children and adults from families with higher purchasing power. 6 Data from the present study is also consistent with that found in Brasilia, in an ISAAC study, which reported a higher prevalence of rhinitis symptoms among adolescents living in areas with a higher socioeconomic level, 25 and supports the hygiene hypothesis, which interprets the variation in risk for allergic illnesses as a reflection of different exposures to infectious agents early in life. 6 We noted, in this study, that the symptoms maintain some continuity, especially in the first half of the yearwhen the rainy season occurs in Fortaleza and when we also observed a higher incidence of respiratory infections.…”
Section: Discussionsupporting
confidence: 90%
“…In the epidemiology of allergic illnesses, the presence of a socioeconomic gradient has been observed, with a higher prevalence of allergic rhinitis and eczema among children and adults from families with higher purchasing power. 6 Data from the present study is also consistent with that found in Brasilia, in an ISAAC study, which reported a higher prevalence of rhinitis symptoms among adolescents living in areas with a higher socioeconomic level, 25 and supports the hygiene hypothesis, which interprets the variation in risk for allergic illnesses as a reflection of different exposures to infectious agents early in life. 6 We noted, in this study, that the symptoms maintain some continuity, especially in the first half of the yearwhen the rainy season occurs in Fortaleza and when we also observed a higher incidence of respiratory infections.…”
Section: Discussionsupporting
confidence: 90%
“…11 The seasonal variation of the prevalence of rhinitis symptoms, like sneezes, runny nose or nasal obstruction, without having a cold, in the past 12 months had higher percentage in the months from June to September and the proportion of children who reported these symptoms in Monte Aprazível was higher than the one reported in other studies. 4 The increase observed in Monte Aprazível occurred during the sugarcane harvest (April to November), consequently with the occurrence of burning outbreaks, which may intensify the pollution levels in the city. This is also the period of winter, which is warm and dry in Monte Aprazível, the period of lowest rainfall index (annual mean rainfall of 113.47 mm, reaching 20 mm in July) and of low air humidity (minimum of 10% during the harvest of 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Estima-se que 15 a 20% da população Brasileira sofram de rinite alér-gica 17 . No Distrito Federal, uma pesquisa realizada com adolescentes mostrou que houve um aumento significante da rinite alérgica diagnosticada em 2006 (20%) em relação a 1996 (12,7%) 18 . Estes resultados, juntamente com os dados da presente pesquisa, apontam para a necessidade de uma maior atenção em relação à rinite nos adolescentes do Distrito Federal, visto que esta patologia é uma das doenças crônicas mais prevalentes na faixa etária escolar, interferindo diretamente na qualidade de vida.…”
Section: Sintomasunclassified
“…Merece ser ressaltado ainda que, apesar de menos da metade da amostra ter referido resfriados constantes dos dois aos doze anos, os principais sintomas da rinite são: espirros em "salvas", prurido nasal, coriza hialina e obstrução nasal, os quais são frequentemente confundidos com resfriados 18 , o que também sugerindo melhor avaliação deste tipo de queixa.…”
Section: Sintomasunclassified